Characterization and discrimination of two varieties of eggplants using multi-element and metabolomics profiles coupled with chemometrics analysis. (December 2022) - Niu, Xuemei; Mi, Si; Jin, Qiuxia; Sang, Yaxin; Wang, Xianghong
Graphical abstract: Highlights: A total of 54 chemical elements were quantified in the samples using ICP-MS. The untargeted metabolomics method based on UHPLC-Q-TOF/ MS was used to measure 365 metabolites in eggplant. Eggplants were separated based on the elemental and metabolomics profiles. Abstract: The main purpose of the present study was to clarify the differences present in the multi-element and metabolite profiles between two varieties of eggplants. A total of 54 elements were identified by inductively coupled plasma mass spectrometry, 16 elements were significantly different between peel (n = 3) and flesh (n = 3). Besides, untargeted metabolomics combined with chemometrics was used to discriminate the peel (n = 4) and flesh (n = 4) of the two varieties of eggplants. A total of 178 metabolites were screened out with criteria of p < 0.05, fold change > 1.5 or < 0.67 and variable importance in projection score > 1 for the PLS-DA model. Maltitol and d -proline were the most important discriminants of the two varieties of eggplants. Kaempferol-3-O-rutinoside was the most important identification components between peel and flesh of the two varieties of eggplant. Results showed that the two varieties of eggplants could be distinguished based on their multi-element and metabolite profiles, which may provide new directions for eggplant function research.